Factors Influencing Employees’ Performance in Hotel Industry at Batu Pahat - Mylvaganam, Kausalya; Zulkipli, Hafizah (Research in Management of Technology and Business, 2023)
Employees are the important asset of our country. Poor and inconsistent performance by employees has led to dissatisfaction, which in turn has led to a drop in their performance, which can endanger the institution's survival, decrease motivation, increase absenteeism, grievances, and turnover, and cause other problems. This research was conducted to determine the factors influencing employees’ performance in hotel industry at Batu Pahat. Employee performance can be explore by investing amounts of energy to factors that upgrade the employee's persuasive level, inventiveness and occupation fulfilment and solace working spot climate. The objectives of this study were to identify the relationship between work environment, empowerment and salary and employees’ performance in hotel industry at Batu Pahat. This research took place around Batu Pahat area for by doing a survey. The scope focus on selected hotels employees with 80 respondents selected from sample frame of 100 employees. Quantitative method has been used in this research by distributing questionnaires to selected hotels. Statistical Package for the Social Sciences SPSS 26 software was applied to test all the findings and hypotheses. This finding has revealed that work environment, empowerment and salary has a significant influence on employees’ performance in hotel industry. The value of determination coefficient correlation between work environment, empowerment and salary and employees’ performance shows a perfect positive correlation.